2005
DOI: 10.1645/ge-454r.1
|View full text |Cite
|
Sign up to set email alerts
|

Epizootiology of Spirorchiid Infection in Green Turtles (Chelonia Mydas) in Hawaii

Abstract: We describe the epizootiology of spirorchiid trematode infections in Hawaiian green turtles (Chelonia mydas) by quantifying tissue egg burdens in turtles submitted for necropsy and by assessing antibody response to crude adult worm and egg antigens among a variety of age groups. Hapalotrema sp. and Laeredius sp. predominated in turtles infected with spirorchiids. Tissue egg burdens decreased with increasing size and increased with deteriorating body condition of turtles. No relationship was found between tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(74 citation statements)
references
References 24 publications
2
67
0
1
Order By: Relevance
“…Gordon et al (1998) found that Cadmium concentrations in green turtles from Australia were up to three times higher than the levels reported in commercial seafood products. The presence of epibionts, parasites (internal and external) might occasionally cause the death of some marine turtles and being predecessors of fibropapiloms (Aguirre y Lutz, 2004;Work, 2000, Work et al, 2005. The presence of fibropapiloms in Hawaiian waters was related with the presence of hirudineans (Díaz, et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Gordon et al (1998) found that Cadmium concentrations in green turtles from Australia were up to three times higher than the levels reported in commercial seafood products. The presence of epibionts, parasites (internal and external) might occasionally cause the death of some marine turtles and being predecessors of fibropapiloms (Aguirre y Lutz, 2004;Work, 2000, Work et al, 2005. The presence of fibropapiloms in Hawaiian waters was related with the presence of hirudineans (Díaz, et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic analyses suggested that a range of unique Neospirorchis genotypes were present, with various site and host affinities evident (Stacy, 2008). While Neospirorchis was the most prevalent spirorchiid genus in this Florida survey, studies from Hawaiian turtles did not detect this genus at all (Work et al, 2005). It is difficult to compare these studies due to differences in sampling method, i.e.…”
Section: Spirorchiid Genera -Host Specificity Tissue Tropisms and Rementioning
confidence: 75%
“…However, significant spirorchiid associated pathology was observed even in robust turtles, indicating that flukes may potentially act as primary pathogens rather than just secondary opportunists (Stacy et al, 2010a). In Hawaii, spirorchiid infections appear to increase with emaciation of the host (Work et al, 2005;Work et al, 2015).…”
Section: Generalmentioning
confidence: 99%
See 2 more Smart Citations